Tren dan Arah Masa Depan E-Commerce: Kajian Sistematis Literatur Tahun 2018–2024 - Fajar Dio Wahyu Tri Amukti; Agus Hermawan (STIKes Ibnu Sina Ajibarang, 2025)
E-commerce has shown very rapid development in recent years as a result of advances in digital technology, changes in consumer preferences, and increasing access to the internet. This study aims to explore the direction of development, challenges, and potential of e-commerce in the future through the Systematic Literature Review (SLR) method of scientific publications published between 2018 and 2024. Of the 203 articles reviewed, 40 articles were selected for further analysis. The results of the study identified five main categories, namely: technological advances (including AI, IoT, and AR), consumer behavior trends, innovations in business models, regulatory and security issues, and opportunities open to MSMEs. The conclusion of the study confirms that the future direction of e-commerce will be largely determined by technology integration, policy adaptability, and business responses to changes in the digital market. These findings are expected to be a reference for academics, business actors, and policy makers in developing inclusive and sustainable e-commerce strategies in Indonesia.